Online Accounting Learning Problems Analysis During the Covid-19 Pandemic - Henny Zurika Lubis; Sulaiman Effendi; Fatmawarni Fatmawarni (Journal of International Conference Proceedings (JICP), 2021)
The purpose of this study was to find out the problems of online learning faced by students and lecturers in the learning process. The Covid-19 Pandemic period has had an impact on learning changes, which usually take place in person or face-to-face, now learning is done only from home through online learning. But on the other hand, the readiness of learning activities at home with online learning has problems from a technical and non-technical perspective. The method used in this research is descriptive qualitative with data collection techniques in the form of literature studies, documentation and questionnaires. learning process, students' difficulties in understanding the material being taught so that students are passive and cause the quality of each individual's task is not good and less than optimal.